의학 전문직업성의 기초자질 함양을 위한 교육과정 평가 및 구성 - 방재범(Jae Beum Bang); 이광윤(Kwang Youn Lee); 이충기(Choong Ki Lee); 이동협(Dong Hyup Lee); 이영환(Young Hwan Lee); 김재룡 (Korean journal of medical education, 2008)
Purpose: Today, the social requirement of medicine emphasizes the importance of medical professionalism. This forces medical educators to introduce new contents and methods into the curriculum. This study aims to offer ideas for developing the curriculum through clarifying priorities on the basic qualities of medical professionalism and evaluating the current curriculums in medical schools in South Korea. Methods: In April 2005, 46 respondents majoring in basic medical sciences, clinical medicine, and medical humanities/social sciences completed a structured questionnaire. The questionnaire consisted of 3 categories related to: 1) the basic qualities of medical professionalism/general education courses, 2) the process of developing the qualities of humanities and social sciences in medical education, and 3) the appropriate allocation of credits for each subject to premedical and medical courses. The analysis consisted of frequency, chi-square, and multiple responses using Korean Ed, SPSS 14.0 for Windows. Results: The most important basic quality is basic medical knowledge. The credits for the general education are sufficient but it's contribution is lacking(44.44%). The most lacking element in the general education courses is socio-cultural comprehension(45.65%). The knowledge of humanities and social sciences is very important in developing the basic qualities(56.52%). The important learning experiences related to these is the introspection into human beings(32.16%). Credits for medical humanities classes in premedical and medical course are noticeably insufficient(45.65, 54.35%, respectively). The appropriate program of informal curriculum for fostering the qualities is meeting with various medical specialists(44.44%, 47.83%, respectively). There is almost no difference among the major groups under(p<.05.) Conclusion: To assist medical students to be equipped with the basic qualities of medical professionalism, the realm of medical humanities should be made mandatory; and the general education courses need to be reformed, especially in the premedical curriculum. In particular, continuous cooperation between faculties in medicine, liberal arts, and/or social sciences need to exist with the conglomeration of these into fewer medical humanities majors in Korea. Purpose: Today, the social requirement of medicine emphasizes the importance of medical professionalism. This forces medical educators to introduce new contents and methods into the curriculum. This study aims to offer ideas for developing the curriculum through clarifying priorities on the basic qualities of medical professionalism and evaluating the current curriculums in medical schools in South Korea. Methods: In April 2005, 46 respondents majoring in basic medical sciences, clinical medicine, and medical humanities/social sciences completed a structured questionnaire. The questionnaire consisted of 3 categories related to: 1) the basic qualities of medical professionalism/general education courses, 2) the process of developing the qualities of humanities and social sciences in medical education, and 3) the appropriate allocation of credits for each subject to premedical and medical courses. The analysis consisted of frequency, chi-square, and multiple responses using Korean Ed, SPSS 14.0 for Windows. Results: The most important basic quality is basic medical knowledge. The credits for the general education are sufficient but it's contribution is lacking(44.44%). The most lacking element in the general education courses is socio-cultural comprehension(45.65%). The knowledge of humanities and social sciences is very important in developing the basic qualities(56.52%). The important learning experiences related to these is the introspection into human beings(32.16%). Credits for medical humanities classes in premedical and medical course are noticeably insufficient(45.65, 54.35%, respectively). The appropriate program of informal curriculum for fostering the qualities is meeting with various medical specialists(44.44%, 47.83%, respectively). There is almost no difference among the major groups under(p<.05.) Conclusion: To assist medical students to be equipped with the basic qualities of medical professionalism, the realm of medical humanities should be made mandatory; and the general education courses need to be reformed, especially in the premedical curriculum. In particular, continuous cooperation between faculties in medicine, liberal arts, and/or social sciences need to exist with the conglomeration of these into fewer medical humanities majors in Korea. KCI Citation Count: 6